Termodinâmica de buracos negros - Gausmann, Evelise [UNESP] (Universidade Estadual Paulista (Unesp), 1996)
Neste trabalho, apresentamos a formulação matemática decorrente da teoria da relatividade geral que segere a analogia entre a física de buracos negros e termodinâmica. Para tornar clara essa analogia, estudamos as quatro soluções de buracos negros conhecidas. Finalmente, analisamos algumas consequências do enunciado das quatro leis da termodinâmica de buracos negros

In this Work, we present the mathematical formulation which results from the general theory of relativity that suggests an analogy between black boles physics and termodynamics theory. In order to make this analogy clear we study the four known solutions which results in black holes. Finally, we analyse some consequences that come out directly from the four laws of the black holes thermodynamic theory
Keywords: Buracos negros (Astronomia) - Termodinâmica; Einstein, Equações de; Relatividade geral (Fisica)